DEVELOPMENT OF APPLICATION MODULES FOR AN ENTERPRISE MANAGEMENT INFORMATION SYSTEM - Balakayeva Г.Т; Bazarbek Ж.П (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This work is devoted to the development of application modules for the enterprise management information system. The purpose of the research work is to increase the efficiency of information exchange. In order to implement a systematic approach, all the essential aspects of the object of research are comprehensively studied. When developing application modules for the enterprise management information system, MongoDB and .NET CORE. To simplify the exchange, preparation, and processing of data, enterprises created databases and used all possible functions. Two modules of the information system have been developed that allow managing the enterprise system-administrative and personnel. The automated system allows you to avoid many errors that occur in the process of data exchange under the influence of human factors. By storing data as savings, we can easily and quickly process and exchange information with multidimensional data.